Functional analyses reveal extensive RRE plasticity in primary HIV-1 sequences selected under selective pressure. - Francesc Cunyat (Public Library of Science (PLoS), 2014)
Background HIV-1 Rev response element (RRE) is a functional region of viral RNA lying immediately downstream to the junction of gp120 and gp41 in the env coding sequence. The RRE is essential for HIV replication and binds with the Rev protein to facilitate the export of viral mRNA from nucleus to cytoplasm. It has been suggested that changes in the predicted secondary structure of primary RRE sequences impact the function of the RREs; however, functional assays have not yet been performed. The aim of this study was to characterize the genetic, structural and functional variation in the RRE primary sequences selected in vivo by Enfuvirtide pressure. Results Multiple RRE variants were obtained from viruses isolated from patients who failed an Enfuvirtide-containing regimen. Different alterations were observed in the predicted RRE secondary structures, with the abrogation of the primary Rev binding site in one of the variants. In spite of this, most of the RRE variants were able to bind Rev and promote the cytoplasmic export of the viral mRNAs with equivalent efficiency in a cell-based assay. Only RRE45 and RRE40-45 showed an impaired ability to bind Rev in a gel-shift binding assay. Unexpectedly, this impairment was not reflected in functional capacity when RNA export was evaluated using a reporter assay, or during virus replication in lymphoid cells, suggesting that in vivo the RRE would be highly malleable. Conclusions The Rev-RRE functionality is unaffected in RRE variants selected in patients failing an ENF-containing regimen. Our data show that the current understanding of the Rev-RRE complex structure does not suffice and fails to rationally predict the function of naturally occurring RRE mutants. Therefore, this data should be taken into account in the development of antiviral agents that target the RRE-Rev complex.